Prevalence and Correlates of Client-Perpetrated Violence against Female Sex Workers in 13 Mexican Cities. - Shirley J Semple; Jamila K Stockman; Eileen V Pitpitan; Steffanie A Strathdee; Claudia V Chavarin; Doroteo V Mendoza; Gregory A Aarons; Thomas L Patterson (PLoS ONE, 2015)
Globally, client-perpetrated violence against female sex workers (FSWs) has been associated with multiple health-related harms, including high-risk sexual behavior and increased exposure to HIV/STIs. This study examined correlates of client-perpetrated sexual, physical, and economic violence (e.g., robbery) against FSWs in 13 cities throughout Mexico.FSWs (N = 1,089) who were enrolled in a brief, evidence-based, sexual risk reduction intervention for FSWs (Mujer Segura) were interviewed about their work context, including experiences of violence perpetrated by clients, sexual risk and substance use practices, financial need, and social supports. Three broad categories of factors (sociodemographic, work context, behavioral and social characteristics of FSWs) were examined as correlates of sexual, physical, and economic violence.The prevalence of different types of client-perpetrated violence against FSWs in the past 6 months was: sexual (11.7%), physical (11.8%), economic (16.9%), and any violence (22.6%). Greater financial need, self-identification as a street worker, and lower perceived emotional support were independently associated with all three types of violence. Alcohol use before or during sex with clients in the past month was associated with physical and sexual violence. Using drugs before or during sex with clients, injection drug use in the past month, and population size of city were associated with sexual violence only, and FSWs' alcohol use score (AUDIT-C) was associated with economic violence only.Correlates of client-perpetrated violence encompassed sociodemographic, work context, and behavioral and social factors, suggesting that approaches to violence prevention for FSWs must be multi-dimensional. Prevention could involve teaching FSWs strategies for risk avoidance in the workplace (e.g., avoiding use of alcohol with clients), enhancement of FSWs' community-based supports, development of interventions that deliver an anti-violence curriculum to clients, and programs to address FSWs' financial need by increasing their economic opportunities outside of the sex trade.